The phosphorylated pathway of serine biosynthesis links plant growth with nitrogen metabolism. Issue 3 (26th May 2021) - Zimmermann, Sandra E; Benstein, Ruben M; Flores-Tornero, María; Blau, Samira; Anoman, Armand D; Rosa-Téllez, Sara; Gerlich, Silke C; Salem, Mohamed A; Alseekh, Saleh; Kopriva, Stanislav; Wewer, Vera; Flügge, Ulf-Ingo; et al.
Abstract: Because it is the precursor for various essential cellular components, the amino acid serine is indispensable for every living organism. In plants, serine is synthesized by two major pathways: photorespiration and the phosphorylated pathway of serine biosynthesis (PPSB). However, the importance of these pathways in providing serine for plant development is not fully understood. In this study, we examine the relative contributions of photorespiration and PPSB to providing serine for growth and metabolism in the C3 model plant Arabidopsis thaliana . Our analyses of cell proliferation and elongation reveal that PPSB-derived serine is indispensable for plant growth and its loss cannot be compensated by photorespiratory serine biosynthesis. Using isotope labeling, we show that PPSB-deficiency impairs the synthesis of proteins and purine nucleotides in plants. Furthermore, deficiency in PPSB-mediated serine biosynthesis leads to a strong accumulation of metabolites related to nitrogen metabolism. This result corroborates 15 N-isotope labeling in which we observed an increased enrichment in labeled amino acids in PPSB-deficient plants. Expression studies indicate that elevated ammonium uptake and higher glutamine synthetase/glutamine oxoglutarate aminotransferase (GS/GOGAT) activity causes this phenotype. Metabolic analyses further show that elevated nitrogen assimilation and reduced amino acid turnover into proteins and nucleotides are the most likely driving forces for changes in respiratory metabolism and amino acid catabolism in PPSB-deficient plants. Accordingly, we conclude that even though photorespiration generates high amounts of serine in plants, PPSB-derived serine is more important for plant growth and its deficiency triggers the induction of nitrogen assimilation, most likely as an amino acid starvation response. Abstract : The phosphorylated pathway of serine biosynthesis is required to synthesize serine for plant growth; and its deficiency triggers an amino acid starvation response by inducing nitrogen assimilation.